Integrasi Nilai Islam dan Inovasi Pembelajaran dalam Pendidikan Agama Islam di Perguruan Tinggi dalam Perspektif Akademik dan Keagamaan - Muhammad Hafizd Fauzi; Salwa Salsabila; Aghnia I'lmi Diniyati; Annisa Rizki Pebriani; Raden Ayu Intan Fithriya; Edi Suresman (Reflection : Islamic Education Journal, 2025)
This research discusses how the integration of Islamic values and learning innovation can be applied in Islamic Religious Education in higher education, especially at the Indonesian Education University. The background of this research is the challenges of globalization and technological developments that require Islamic education to continue to innovate without ignoring the principles of sharia. This research uses a qualitative approach with a case study method, involving lecturers, students, and religious leaders as informants. The results showed that the integration of Islamic values in Islamic education is done through the Islamization of science approach, the use of technology in learning, and the creation of a religious academic environment. In addition, innovations such as Problem-Based Learning and Experiential Learning methods proved to be able to increase students' interest and understanding of Islamic teachings. In conclusion, collaboration between academics, students, and religious leaders is very important in creating Islamic Religion Education learning that is relevant, interesting, and still in accordance with Sharia law. This research is expected to provide an overview and strategic recommendations for the development of Islamic education in the modern